Can miR-145-5p be used as a marker in diabetic patients?. (3rd September 2022) - Shahrokhi, Seyedeh Zahra; Saeidi, Leyla; Sadatamini, Mirsaber; Jafarzadeh, Meisam; Rahimipour, Ali; Kazerouni, Faranak
Abstract: In the light of emerging global epidemics of type 2 diabetes mellitus significant efforts are continuing to discover novel biomarkers for early detection of the disease. Since miRNAs play an important role in both the initiation and progress of many pathologic processes such as diabetes, in this study we aimed to evaluate expression level of plasma miR-145-5p in diabetics and pre-diabetics in comparison to the control group and assess its use as a biomarker in diagnosis of T2D. The plasma level of miR-145-5p was assessed in three groups including 20 prediabetic patients, 20 T2D patients and 20 healthy controls using RT-qPCR. Biochemical parameters were also measured by the auto-analyzer. Expression level of miR-145-5p was down-regulated in the prediabetics and the T2D patients compared to the controls. In the control group miR-145-5p showed a borderline correlation with FBS ( p   =  .06), while in the prediabetic group miR-145 showed a significant negative correlation with FBS and finally in the T2D patients miR-145 was negatively correlated with HbA1c and TC and showed a negative borderline correlation with FBS. The ROC analysis indicated a significant ability for miR-145-5p in discriminating between the diabetics and pre-diabetics from the healthy subjects. Our results demonstrated that the miR-145-5p expression level is deregulated in the diabetics and the prediabetics. Furthermore miR-145-5p displayed a significant ability to discriminate the diabetics from the healthy subjects. These results suggest that miR-145-5p may be a useful biomarker for the diagnosis of T2DM.